Memperkuat Landasan dan Prinsip Pendidikan untuk Pengembangan Profesionalisme Guru Matematika Abad ke-21 - Zahra Elfa Yuda, Sauzan; Laksmana Cs, Andini; Afrida, Anni; Hapsari, Nadila Tri; Sagougouk, Olensius; Suryani, Mulia (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
Twenty-first century education demands mathematics teachers to possess professionalism grounded in philosophical, psychological, sociological foundations and educational principles to effectively address the dynamics of digital-based and character-oriented learning. This study aims to analyze the urgency of strengthening educational foundations and principles in developing the professionalism of mathematics teachers in the 21st century. This research employed a qualitative approach with a library research method. Data were obtained through systematic literature reviews, journal articles, reference books, and educational policy documents, then analyzed using content analysis techniques. The results indicate that strengthening educational foundations encompassing philosophical, psychological, sociological, historical, and juridical aspects serves as a conceptual basis in determining educational policy directions, objectives, and practices that are humanistic, contextual, and aligned with contemporary demands. Meanwhile, educational principles function as normative guidelines in educational practice, such as the principles of humanism, democracy, justice, freedom, activeness, and relevance. The integration of these two elements significantly contributes to enhancing mathematics teachers' adaptive abilities in facing classroom dynamics, technological developments, and shifts in educational policy. Strategies for strengthening teacher professionalism can be optimized through value-based training, MGMP-based lesson study, digital learning communities, and the Teacher Professional Education (PPG) program. These findings recommend the importance of designing systematic, collaborative, and value-oriented teacher professionalism development programs to build a national education system that is adaptive, competitive, and character-driven